Crenças sobre as causas do infarto agudo do miocárdio e autocuidado - Sá, Nivaldete de Oliveira (Universidade do Vale do Rio dos Sinos, 2019)
The present dissertation deals with the subject of disease perception and self-care, whose general objective was to investigate self-care and the beliefs of causal attributions regarding acute myocardial infarction-AMI in sick and healthy people. With this, it is sought to contribute to the expansion of research in the area of Health Psychology, specifically, in the psychological and behavioral factors involved in the process of illness. The dissertation is composed of a theoretical and an empirical article. In article 1, we sought to discuss self-care for AMI prevention. These are theoretical considerations regarding self-care as central to promoting health and well-being and for prevention of AMI and adherence to treatment. In addition, it shows the relevance of the health professional to know and understand about this issue. Article 2 is empirical, with a cross-sectional and comparative design, aimed at examining the beliefs about the causes of AMI and the self-care behavior of people with and without the disease. Thirty-one people with AMI and forty six people without this disease, living in the interior of Maranhão, participated in this study. Participants answered to sociodemographic questionnaires, self-care behavior, and causes of the disease. The results indicate that people with and without disease had very similar beliefs regarding the causes of AMI. Thus, it is concluded that the experience of the disease needs to be accompanied by a better understanding of AMI in order to achieve adequate treatment.
Keywords: Infarto agudo do miocárdio; Doenças cardiovasculares; Crenças em saúde; Atribuição causal; Autocuidado; Acute myocardial infarction; Cardiovascular diseases; Health beliefs; Cause attribution; Self-care; ACCNPQ::Ciências Humanas::Psicologia